Sri Lanka's "Army of Housemaids": Control of Remittances and Gender Transformations - Gamburd, Michele Ruth (Anthropologica, 2022)
When the mass labour migration of women to the Middle East began in the early 1980s, many Sri Lankan social scientists predicted a revolution in gender equality and a greater participation by women in political and economic decision-making as a result of employment abroad. Noting that gender rarely correlates in predictable ways with social change, and questioning the dominant teleological ideology that change always happens for the better, this article looks at relations between female migrants in a coastal village in the Southwest and the people responsible for spending and saving the money they remit to the village. Several case studies reveal the extent to which men have not taken over tasks such as child care and household chores. In all-male drinking groups, unemployed husbands reassert their masculinity in the face of their wives' new role as breadwinner. The values of the drinking community stand in implicit opposition to values channelling family resources towards "getting developed" (diyunu vengyaa), the dominant village idiom of successful migration. Several women's stories document their struggles, including the ultimate protest of a suicide attempt, to control the money they send back to the village. In cases where women's work has bettered their family's economic standing in the village, women and their husbands and fathers enjoy new social privileges and authority. Finally, migration as an avenue of escape provides a new option for women caught in untenable home situations. By examining the gendered power dynamics of the microprocesses of social change, this article explores the extent to which women's lives have and have not improved through migration.